Funkcje teorii środków produkcji materialnej w badaniu formacji społeczeństw współczesnych - Kozyr-Kowalski, Stanisław (Wydział Prawa i Administracji UAM, 1982)
The article brings the first series of arguments for the interpretation of a thesis, inherent in the historical materialism, on defining a social formation by the economic structure. That proposition was put forward in the treatise on "The Theory of Material production Means and the Modern Societies" (Ruch Prawniczy, Ekonomiczny i Socjologiczny nr 3/82). Application of the theory of means of production, as a tool to identify economy, results in questioning the common opinion that a role of State is increasing in the socialist societies along with the diminishing range and importance of the economic structure. When that theory is applied as a method of initial definition of peculiarities of extraeconomic structures of the social formation one is able to criticise the common concept of State. The Marxist notion of legal and political superstructure can not be reduced to the colloquial term of "State". The author distinguishes three large processes by which the structure of production means is conditioning all the extraeconomic regions of the social formation: 1) natural effect of material goods- manufactured by means of production on a biological organism of a human being (analysis of that process implies the application of historical materialism along with the discoveries of modern natural), 2) tellic conditioning (linking the historical materialism with problems of modern theories of social action, practice and "humanistic sociologies" as opposed to the sociological naturalism), 3) mental reproduction of the objective world (analysis of that process assumes materialistic and historical sociology of knowledge, the sociology of extrascientific and scientific cognition). Application of the theory of means of production as a tool examing the influence of some non- economic structures on the economic structure allows a transition from formulating pre-scientific queries: can law, science, art and ideas influence the economy? to scientific questions: what are the processes which account for the influence of a superstructure on a base? The exact indicators of that influence can also be seen. The analysis of the position of economy on the formation of modern societies indicates at numerous arguments bearing on the merits of the proposition that the historical materialism has presently more significance for the scientific study of economy as a whole, and of society as a whole than it used to have in the times of Marx and Lenin.
Functions of the Theory of Means Material Production m Studies on the Formation of Modern Societies